2017
DOI: 10.1001/jamafacial.2017.0070
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increasing Nasal Tip Projection With Lip Position in Primary Rhinoplasty

Abstract: ip modification is an integral part of rhinoplasty. It is arguably the most difficult and complex part of the procedure owing to the many variables that can be altered. Besides changing the shape of the nasal tip, several of the maneuvers in rhinoplasty involve changing the tip location, whether that is projection and/or rotation. These alterations are used during both cosmetic and functional rhinoplasty. Although several studies have focused on evaluating how tip modifications affect other regions of the nose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…16 The importance of current study was the assessment of lip position in profile view. Cerrati et al (2017) evaluated the increased nasal tip projection on lip position. 6 They assessed the lip position at the level of vemillion and concluded that upper lip would be more projected as the nasal tip projection is increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 The importance of current study was the assessment of lip position in profile view. Cerrati et al (2017) evaluated the increased nasal tip projection on lip position. 6 They assessed the lip position at the level of vemillion and concluded that upper lip would be more projected as the nasal tip projection is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Cerrati et al (2017) evaluated the increased nasal tip projection on lip position. 6 They assessed the lip position at the level of vemillion and concluded that upper lip would be more projected as the nasal tip projection is increased. 6 The other anatomical landmark that should be considered in evaluating the lip position in profile view is subnasal area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diğer yandan yaptıkları 20 hastayı içeren çalışmada, ÜDP'nin tip cerrahisi menevralarıyla artışı sonucu "Z" açısının azaldığını vurgulamışlardır. 18 Çalışmamızın sonuçları da Cerrati ve Dayan'ın çalışmasıyla aynı paralellikte nazal tip rotasyonu ve projeksiyonunun ÜDP üzerinde artırıcı, Z açısında azaltıcı bir etki oluşturduğunu göstermektedir. Bu bilgilerden yola çıkarak, tip rotasyonu sonucu oluşan üst ÜDP artışının, hastalara daha genç bir görünüm sağlayabileceği sonucu çıkartılabilir.…”
Section: Bulgularunclassified